PROBLEMS OF TEACHING A FOREIGN LANGUAGE IN UZBEKISTAN AND THEIR SOLUTIONS - Yunusova , Holida (Educational Research in Universal Sciences, 2023)
The study aimed to identify the problems encountered by B1-B2 level learners studying Turkish as a foreign language, specifically related to language learning skills. The data was collected through open-ended questions and analyzed using content analysis. The results of the study identified problems in reading, listening, speaking, and writing skills, as well as difficulties in learning grammar rules and new words. This research contributes to the understanding of the challenges faced by TFL learners and can inform the development of teaching materials and approaches to address these issues.